2021
DOI: 10.3390/en14041010
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Commercial Energy Consumption Intention of Rural Residents: Evidence from Rural Chengdu

Abstract: With rapid rural urbanization and new rural construction, the commercial energy consumption of rural residents shows a trend of rapid growth, and China’s rural areas are also faced with environmental challenges brought by the increase of commercial energy consumption. China’s commercial energy consumption behavior of rural residents has also undergone tremendous changes. However, scholars have neglected the research on rural residents’ commercial energy consumption intention from a micro perspective. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, our study identified a significant positive relationship between behavioral intention and actual behavior, supporting the notion that intention serves as a reliable predictor of subsequent behavior. This finding aligns with previous studies on environmental conservation behaviors ( Zhong et al, 2019 ; Jiang et al, 2021 ; Baghernejad et al, 2023 ) and underscores the relevance of understanding and targeting individuals’ intentions to promote their engagement in forest management activities.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our study identified a significant positive relationship between behavioral intention and actual behavior, supporting the notion that intention serves as a reliable predictor of subsequent behavior. This finding aligns with previous studies on environmental conservation behaviors ( Zhong et al, 2019 ; Jiang et al, 2021 ; Baghernejad et al, 2023 ) and underscores the relevance of understanding and targeting individuals’ intentions to promote their engagement in forest management activities.…”
Section: Discussionsupporting
confidence: 90%
“…Model 1 in Table 3 shows the return outcome of whether the household head had college education or above as the basis for grouping; it can be seen from the results that the off-farm employment of the labor force under the two groups was both significantly related to the use of clean energy for farmers' cooking; however, it is noted that LOE for farmers with college education and below was more obvious in promoting the use of CCE (2.229 > 0.853). The possible reasons are that the education level of the household head affects the family's energy consumption understanding, environmental protection awareness, and health awareness, which leads to differences in the use of clean energy [63]. For the farmers whose household head education level was university or above, the highly educated family's ideas and consumption understanding had been greatly influenced, so the LOE was not a great way to improve their consumption understanding.…”
Section: Heterogeneity Analysismentioning
confidence: 99%
“…For example, Zi et al (2021) found that “gas + electricity” has become a common cooking energy combination mode in rural areas of Henan Province, with 33% of farmers using this combination of energy for cooking [ 16 ]. Jiang et al (2021) found that subjective norms, perceived behavioral control and habits have significant impacts on residents’ behavioral intentions [ 17 ]. Ma et al (2019) found that off-farm income promoted the change in the energy structure of farmers, significantly increasing the use of electricity and natural gas and reducing the use of traditional biomass energy [ 13 ].…”
Section: Introductionmentioning
confidence: 99%